A HYBRID APPROACH TO LEARNING BASED ON EMOTIONAL EXPERIENCE AND THE DEVELOPMENT OF INNOVATIVE METATHINKING IN POST-WAR UKRAINE - MYGAL , S. P.; MYGAL, V.P.; MYGAL, G.V. (Art and Design, 2024)
Purpose of the study is to synthesize generalized metaheuristic and metacognitive models, the use of which in project culture contributes to the formation of innovative creative-critical metathinking of an individual. Methodology. The methodology for studying creative activity and training of a designer is based on the post-neoclassical paradigm of scientific knowledge, subject-object integrity of the system of relations and dialectically developing relationships in a hybrid innovative learning environment. The methodology also includes new methods of interdisciplinary research and modeling of reality, integrating physical and social ontology. It is shown that the development of a structural-functional approach to the perception of physical and digital reality takes into account the peculiarities of an individual’s brain activity. Results. The main results obtained are a triad of generalized author’s metamodels, namely: 1. A heuristic metamodel of post-neoclassical perception of physical reality by a designer, in which the independence of cognition cycles, as well as the complementarity of paradigms (synergetic, triadic and semiotic) combines physical and social ontology, which creates new opportunities for the formation of a designer’s creative metathinking in the process of experience. activity. 2. A heuristic metamodel of post-neoclassical perception and reflection of physical and virtual reality by a conceptual designer, in which the dependence of cycles of cognition, as well as the complementarity of heuristic metamodels, is achieved through universal triangles (fractal, Pascal, Sierpinski), the structures of which contribute to innovative activity of the conceptual designer. 3. Cognitive meta-model for the formation of meta-thinking of a designer-conceptualist, which is based on the spatio-temporal balance of explicit and hidden relationships, the cognitive visualization of which contributes to the search for harmony in the process of experience-oriented learning and creative activity through semiotic tools. Scientific novelty is determined by the complementarity of the structures of the author’s metamodels of physical and digital reality, the synergy of which contributes to the optimization of experience-oriented models of teaching and self-learning. The interrelation of the structures of metamodels and their complementarity is the basis of successful activities in a hybrid learning environment (real physical and virtual mathematical), which facilitates the transfer of emotional and intellectual content between objects and subjects of the digital world. Practical significance of complementarity and interconnection of new metamodels of metathinking allows us to develop: universal criteria for determining the quality of design objects using GenAI; a method for identifying triads of interconnected opposites in information sources of various natures, the visualization of which simplifies interdisciplinary interaction between designers; create a personal e-assistant, e- consultant, e-expert using GenAI. In post-war Ukraine, interdisciplinary exchange of ideas, methods and successful experiences is extremely relevant within the framework of a hybrid approach to understanding the harmony of physical and digital reality, which promotes successful creative activity based on the perception of the harmony of nature to achieve the unattainable. Further development of experiential learning through the formation of metathinking is necessary to improve mental health and adapt to inevitable social transformations.